Search for manifestations of new physics in fermion-pair production at LEP - Dova, María Teresa (2000)
The measurements of hadron and lepton-pair production cross sections and leptonic forward–backward asymmetries performed with the L3 detector at centre-of-mass energies between 130 GeV and 189 GeV are used to search for new physics phenomena such as: contact interactions, exchange of virtual leptoquarks, scalar quarks and scalar neutrinos, effects of TeV strings in models of quantum gravity with large extra dimensions and non-zero sizes of the fermions. No evidence for these phenomena is found and new limits on their parameters are set.